a, 3\(^x\).3 = 243
3\(^x\) = 243: 3
3\(^x\) = 81
3\(^x\) = 34
\(x\) = 4
b, \(x^{20}\) = \(x\)
\(x^{20}\) - \(x\) = 0
\(x\)(\(x^{19}\) - 1) = 0
\(\left[{}\begin{matrix}x=0\\x^{19}=1\end{matrix}\right.\)
\(\left[{}\begin{matrix}x=0\\x=1\end{matrix}\right.\)
vậy \(\in\) {0; 1}
c, 2\(^x\).162 = 1024
2\(^x\) = 1024: 162
2\(^x\) = 210: 28
2\(^x\) = 22
\(x\) = 2
d, 64.4\(^x\) = 168
4\(^x\) = 168:64
4\(^x\) = (42)8 : 43
4\(^x\) = 413
\(x\) = 13
e, 2\(^x\).4 = 128
2\(^x\) = 128:4
2\(^x\) = 32
2\(^x\) = 25
\(x\) = 5